Religiosity, financial literacy, and frugal living: A holistic pathway to sustainable wealth among young Muslim entrepreneurs - Nuril Badria; Naimatul Hasanah; Moh. Amin (JEMA: Jurnal Ilmiah Bidang Akuntansi dan Manajemen, 2024)
In recent years, a growing trend among young entrepreneurs to showcase their achievements through hedonistic displays of wealth has emerged, contradicting the core Islamic values of moderation and humility. While most studies have explored the influence of religious values on consumer behavior, research focusing specifically on Muslim entrepreneurs' behavior remains scarce. This study investigates the roles of religiosity, financial literacy, and frugal living intention in building sustainable wealth among young Muslim entrepreneurs in Indonesia. The study collected data from 200 respondents, consisting of Muslim entrepreneurs aged 20–35 years who owned and managed small to medium-sized enterprises in Indonesia. The relationships among these variables were analyzed using path analysis, supported by the bootstrapping technique through Hayes Process. The findings reveal that religiosity plays a significant role in shaping frugal living intentions, driven by Islamic teachings that advocate for simplicity, self-discipline, and ethical accountability. This means that the higher the level of religiosity, the stronger the inclination toward adopting a frugal lifestyle, as individuals are guided by spiritual principles to prioritize mindful and ethical financial behaviors.  Financial literacy further reinforces this relationship by equipping young entrepreneurs with the necessary skills and knowledge to align their financial decisions with their spiritual values.